The evolution of secondary metabolism – a unifying model - Firn, Richard D.; Jones, Clive G. (Molecular microbiology, 2000)
Why do microbes make secondary products? That question has been the subject of intense debate for many decades. There are two extreme opinions. Some argue that most secondary metabolites play no role in increasing the fitness of an organism. The opposite view, now widely held, is that every secondary metabolite is made because it possesses (or did possess at some stage in evolution) a biological activity that endows the producer with increased fitness. These opposing views can be reconciled by recognizing that, because of the principles governing molecular interactions, potent biological activity is a rare property for any molecule to possess. Consequently, in order for an organism to evolve the rare potent, biologically active molecule, a great many chemical structures have to be generated, most of which will possess no useful biological activity. Thus, the two sides of the debate about the role and evolution of secondary metabolism can be accommodated within the view that the possession of secondary metabolism can enhance fitness, but that many products of secondary metabolism will not enhance the fitness of the producer. It is proposed that secondary metabolism will have evolved such that traits that optimize the production and retention of chemical diversity at minimum cost will have been selected. Evidence exists for some of these predicted traits. Opportunities now exist to exploit these unique properties of secondary metabolism to enhance secondary product diversity and to devise new strategies for biotransformation and bioremediation.